Microstructural chromosome reorganization in the genus Trichomycterus (Siluriformes: Trichomycteridae) - Oliveira, Maria Ligia M. de [UNESP] (2016)
Trichomycterus is a specious fish genus within Trichomycterinae and displays remarkable karyotype diversity. However, knowledge about their genomic structure and location of repetitive sequence is still limited. In order to better understand the karyotype diversification, we analyzed nine species of Trichomycterus using classical and molecular cytogenetic techniques. Results revealed a conserved diploid chromosome number of 2n=54 chromosomes in all analyzed species, although remarkable differences on the constitutive heterochromatin distribution were observed. In addition, while the 18S rDNA showed a conserved distribution pattern, the 5S rDNA sites showed a quite diverse location considering the analyzed species. Remarkably, both ribosomal genes were co-located in all species, except in T. iheringi, suggesting that co-localization is probably an ancestral condition in Trichomycterus. Finally, three analyzed species showed heterochromatic B chromosomes, reinforcing the intense genomic reorganization occurring in Trichomycterus. Our results showed that chromosomal variations are not restricted to differences in karyotype formula as previously proposed, but also to modifications on the microstructural level of resolution.